A Network of One's Own: Young Women and the Creation of Youth-only Transnational Feminist Spaces. (May 2017) - Hunt, Theresa A.
In the last decade, young people have been at the fore of spectacular global protests, from revolutions across North Africa to the Occupy Wall Street movements spreading across Europe and North America. Youth involvement in these protests has interested major media and the scholarly community, but few have thoroughly interrogated young women's distinct formations of transnational, youth-only feminist networks. This study, which employed qualitative methods influenced by grounded theory, offers insight into the motivations and operations of five young women's transnational feminist networks (TFNs). Key findings include young feminists' articulations of encountering marginalization, both age and gender based, in existing and established networks, and creating 'youth-only' feminist networks in response. Coalescing around these experiences of marginalization, young women perceive their networks to constitute a 'counter-public sphere' through which they can engage in praxis-oriented discourses, and to constitute a space in which to experiment with and deliberate new or alternative movement repertoires.